Sintomas urinário em idosos com dor lombar inespecífica: estudo exploratório da ocorrência e dos fatores associados - Juliana Magalhães Machado Barbosa (2022)
Low back pain (LBP) is a prevalent and relevant condition in the older people. It is associated with a number of conditions that can increase the possibility of urinary symptoms (US), among which is urinary incontinence (UI). The LBP can be associated with UI by means of clinical conditions, effects on lifestyle habits, functional and biomechanical repercussions. The aging process and senility may make the relationship between LBP and US in the older people different. Objective: to identify the occurrence of US and UI in older people with LBP and to explore the factors associated with the relationship between LBP and UI. Development: The occurrence of US and associated factors were analyzed using baseline data from the BackComplaints in the Elders Project (BACE) – Brazil. The results are presented in Article1, which is in the already published journal Neurourology and Urodinamics entitled: “Urinary symptoms in older people with low back pain - Prevalence, clinical, and functional factors associated”. The occurrence of urinary symptoms was 18.4% identified in a sample of 586 older people with nonspecific acute low back pain. US were associated with depressive symptoms (OR 2.84, 95%CI 1.66-4.86), low gait speed (OR = 0.33; 95%CI 0.14–0.78) and LBP-related disability (OR = 1.09; 95%CI 1.04–1.13). Subsequently, it was decided to investigate the occurrence of UI in the 10- year follow-up of the BACE-B and to include biomechanical variables - posture, pelvic stability, trunk range of motion (ROM) and pelvic floor muscle functions (PFMs). For the operationalization of this stage, it was necessary to evaluate the reliability of two instruments for the older person. The article 3, entitled “Clinimetric Properties of inclinometer for spine range of motion in older adults: reability, minimum detectable change and standard error of measurement”, was submeted to São Paulo Medical Journal and tested the reliability of the analog inclinometer to assess trunk range of motion in 29 community-dwelling older people. The instrument showed excellent classification for the intra (ICC = 0.85 - 0.95) and inter-examiner (0.73-0.94) reliability, except for the extension movement, which was classified as good. The SEM ranged from 1.39° (right lateral flexion) to 2.12° (extension) and the MDC95 ranged from 3.85° (left lateral flexion) to 5.13° (left lateral flexion). Article 3, entitled “Clinimetric properties of the postural assessment software in older people”, which has already been submitted to the journal Geriatrics, Gerontology and Aging, showed that the Postural Assessment Software (SAPO) achieved, in most angles, good to excellent classification for the intra- and inter-rater reliability (ICC = 0.34-0.81 and ICC = 0.33- 0.88, respectively). The standard error of measurement (SEM) was less than 100 at most angles and the minimum detectable difference (MDC95) ranged from 2.88º to 18.49º. Side view angles achieved better levels of reliability.The occurrence of UI (International Consultation on Incontinence Questionnaire-Short Form) in the 10-year of the BACE-Project and the associated demographic, clinical-functional and biomechanical factors were evaluated and the results are presented in Article 4 entitled: “Urinary incontinence in the older people with low back pain - occurrence and associated factors: data from the Back Complaints in the Elders- BACE-Brasil”. The results showed that 61.62% of the older people with chronic nonspecific LBP reported UI, of which 51.4% complained of urge UI symptoms. Factors associated with UI were: age (OR 1.04, CI95% 1.00-1.08), “active” physical activity level (OR 0.43, CI95% 0.19- 0.97), LD-related disability (OR 2.14, CI95% 1.05-4.36) and decreased trunk flexion range of motion (OR 0.95, CI95 % 0.95-0.99). Conclusion: Older patients with acute LBP had a occurrence of 18.4% of US, associated with depressive symptoms, low gait speed and disability related to LBP. SAPO obtained acceptable indices of inter and intra-evaluator reliability for most measures, especially in the lateral view. The ROM measurements with an analog inclinometer reached adequate levels of reliability for the older people. Older patients with non-specific chronic LBP had a occurrence of UI of 62.32%, associated with increasing age, physical activity level, LBP-related disability and decreased trunk flexion ROM.